2020
DOI: 10.7554/elife.61388
|View full text |Cite
|
Sign up to set email alerts
|

POMK regulates dystroglycan function via LARGE1-mediated elongation of matriglycan

Abstract: Matriglycan [-GlcA-β1,3-Xyl-α1,3-]n serves as a scaffold in many tissues for extracellular matrix proteins containing laminin-G domains including laminin, agrin, and perlecan. Like-acetylglucosaminyltransferase-1 (LARGE1) synthesizes and extends matriglycan on α-dystroglycan (α-DG) during skeletal muscle differentiation and regeneration; however, the mechanisms which regulate matriglycan elongation are unknown. Here, we show that Protein O-Mannose Kinase (POMK), which phosphorylates mannose of core M3 (GalNac-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 43 publications
(141 reference statements)
1
34
0
Order By: Relevance
“…Such competing action of the two enzymes eventually influences the resulting affinity towards laminin and other α-DG binding partners in different tissues [ 21 ]. A further complexity in the control of matriglycan synthesis emerged with the recent finding that also the kinase POMK is needed to regulate the LARGE1-mediated elongation of matriglycan [ 22 ].
Figure 1 A scheme of the M3 core carbohydrate chain and its specific carbohydrate blocks ( a ) and of the progressive enzymatic cascades present in the ER and Golgi apparatus ( b ).
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such competing action of the two enzymes eventually influences the resulting affinity towards laminin and other α-DG binding partners in different tissues [ 21 ]. A further complexity in the control of matriglycan synthesis emerged with the recent finding that also the kinase POMK is needed to regulate the LARGE1-mediated elongation of matriglycan [ 22 ].
Figure 1 A scheme of the M3 core carbohydrate chain and its specific carbohydrate blocks ( a ) and of the progressive enzymatic cascades present in the ER and Golgi apparatus ( b ).
…”
Section: Introductionmentioning
confidence: 99%
“…The last step of this ER enzymatic phase is carried out by POMK (SGK196), a kinase that works with ATP as a donor substrate and is involved in the phosphorylation of the M3 glycan mannose on its C-6 position [ 44 ]. Three-dimensional structures of POMK have been solved [ 45 , 46 ], and it was recently shown that LARGE1 (see paragraph 1.3) can work efficiently only when POMK is active [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their amino acid sequences were well enough conserved with the canonical kinases for them to be classified as kinases. POMK is an O-mannose kinase important for dystroglycan receptor function and matriglycan elongation ( 18 , 20 ). VLK is the first secreted tyrosine kinase identified, and it phosphorylates a broad range of secreted and ER-resident substrates ( 19 ).…”
Section: Secreted Kinasesmentioning
confidence: 99%
“…NG2 PG binds type V and VI collagen through its central non-globular domain ( Clarke et al, 2012 ; Huang et al, 2014 ) and with integrins ( Sakry and Trotter, 2016 ). C-terminal LamG domains of NG2 interact with BM components and are crucial for formation of synaptic neuroligin-neurexin complexes and glial cell signaling ( Jeong et al, 2017 ) and also interact with matriglycan-dystroglycan, perlecan, agrin and type XVIII collagen to localize NG2PG in motor neuron endplates in the neuromuscular junction (NMJ) ( Walimbe et al, 2020 ).…”
Section: Other Non-lectican Large Neural Proteoglycansmentioning
confidence: 99%